Novel Microdeletion in the X Chromosome Leads to Kallmann Syndrome, Ichthyosis, Obesity, and Strabismus - Ma, Wanlu; Mao, Jiangfeng; Wang, Xi; Duan, Lian; Song, Yuwen; Lian, Xiaolan; Zheng, Junjie; Liu, Zhaoxiang; Nie, Min; Wu, Xueyan (Frontiers in Genetics, 2020)
Background A large deletion in Xp22.3 can result in contiguous gene syndromes, including X-linked ichthyosis (XLI) and Kallmann syndrome (KS), presenting with short stature, chondrodysplasia punctata, intellectual disability, and strabismus. XLI and KS are caused by the deletion of STS and ANOS1 , respectively. Method Two KS patients with XLI were screened to identify possible pathogenic mutations using whole exome sequencing. The clinical characteristics, molecular genetics, treatment outcomes and genotype-phenotype association for each patient were analyzed. Results We identified a novel 3923 kb deletion within the Xp22.31 region (chrX:5810838-9733877) containing STS, ANOS1, GPR143, NLGN4X, VCX-A, PUDP, and PNPLA4 in patient I, who presented with KS, XLI, obesity, hyperlipidemia, and strabismus. We identified a novel 5807 kb deletion within the Xp22.31-p22.33 regions (chrX:2700083-8507807) containing STS, ANOS1, and other 24 genes in patient II, who presented with KS, XLI, obesity, and strabismus. No developmental delay, abnormal speech development or autistic behavior were noticed in either patient. Conclusion We identified two novel microdeletions in the X chromosome leading to KS and XLI. These findings contribute to the understanding of the molecular mechanisms that drive contiguous gene syndromes. Our research confirmed that the Kallmann-Ichthyosis phenotype is caused by microdeletions at the chromosome level.